1986
DOI: 10.1007/bf01871194
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Na+/K+/Cl− cotransport system in basolateral membrane vesicles from the rabbit parotid

Abstract: Sodium (22Na) transport was studied in a basolateral membrane vesicle preparation from rabbit parotid. Sodium uptake was markedly dependent on the presence of both K+ and Cl- in the extravesicular medium, being reduced 5 times when K+ was replaced by a nonphysiologic cation and 10 times when Cl was replaced by a nonphysiologic anion. Sodium uptake was stimulated by gradients of either K+ or Cl (relative to nongradient conditions) and could be driven against a sodium concentration gradient by a KCl gradient. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 36 publications
4
55
1
Order By: Relevance
“…Since physiological studies with salivary glands have indicated that 99mTcO-is handled in a manner analogous to radioiodide (7,8), we also attempted to study the effect ofreplacing C1-in HBSS-H with I-. Although we observed a significant inhibition of 99mTcO-uptake (75%) when C1-was replaced with I-in HBSS-H, we found that non- (16) and is quite similar to comparably characterized C1-co-transport mechanisms found in the shark rectal gland (17,18) and the rabbit thick ascending limb of Henle's loop (19). We show here that "mTcO uptake by rat parotid cell aggregates is very rapid, mimicking closely the time course of 36C1-uptake in the same preparation (15).…”
Section: Resultscontrasting
confidence: 74%
“…Since physiological studies with salivary glands have indicated that 99mTcO-is handled in a manner analogous to radioiodide (7,8), we also attempted to study the effect ofreplacing C1-in HBSS-H with I-. Although we observed a significant inhibition of 99mTcO-uptake (75%) when C1-was replaced with I-in HBSS-H, we found that non- (16) and is quite similar to comparably characterized C1-co-transport mechanisms found in the shark rectal gland (17,18) and the rabbit thick ascending limb of Henle's loop (19). We show here that "mTcO uptake by rat parotid cell aggregates is very rapid, mimicking closely the time course of 36C1-uptake in the same preparation (15).…”
Section: Resultscontrasting
confidence: 74%
“…These effects of bumetanide are duplicated by the removal of medium chloride (Fig. 2), a maneuver which would also result in suppression of Na'-K+-2Cr-cotransport activity (6). Furthermore, when the acinar cells are alkalinizedby propionate removal rather than NH' addition, as in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Studies from a number of laboratories, including our own, indicate that a Na+-K+-2Cl-cotransporter is responsible for driving the bulk ofthe acinar chloride secretion associated with fluid production in salivary glands (3)(4)(5)(6)(7). This process is thought to conform to the following scheme (8,9).…”
Section: Introductionmentioning
confidence: 98%
“…The new pellet was saved as fraction 2, and the supernatant was centrifuged at 200,000g for 1 h to yield a pellet that was saved as fraction 3. ␥-Glutamyltranspeptidase was used as a marker for the APM (Paul et al, 1992) and K ϩ -stimulated p-nitrophenyl phosphatase was used as a marker for the basolateral plasma membrane (Turner et al, 1986) as described previously. The specific activity of ␥-glutamyltranspeptidase for fractions 1, 2, and 3 was 375 Ϯ 5.6, 18.3 Ϯ 0.9, and 28.5 Ϯ 2.7 nmol/ min/mg of protein, respectively.…”
Section: Methodsmentioning
confidence: 99%